2006
DOI: 10.1021/jf061602q
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Italian Multifloral Honeys Reduce the Extracellular Ferricyanide in Human Red Blood Cells

Abstract: In this study we investigated some biological properties of flavonoids recovered in the aqueous (AqE) and ether (EtE) extracts from four Italian multifloral honeys. In particular, a cell-free assay was employed to detect direct reduction of ferricyanide, whereas an assay using intact human erythrocytes was used to measure the ability to donate electrons to a trans-plasma membrane oxidoreductase. It was found that the AqE displays greater "in vitro" ferricyanide-reducing activity than the EtE but, unlike the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 45 publications
5
43
1
2
Order By: Relevance
“…Our results show the anti-inflammatory role of acacia honey by its ability to down regulate the level of TNF α in PC-3 cell line. This support the anti-inflammatory role of honey as previously described [11]. The level of IL-1β was observed to be high in our present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results show the anti-inflammatory role of acacia honey by its ability to down regulate the level of TNF α in PC-3 cell line. This support the anti-inflammatory role of honey as previously described [11]. The level of IL-1β was observed to be high in our present study.…”
Section: Discussionsupporting
confidence: 93%
“…It is a promising antitumor agent with pronounced anti-metastatic and anti-angiogenic effects [10], antibacterial, anti-inflammatory, immune-stimulant, antiulcer and wound/burn healing effects [11]. Various signaling pathways, including stimulation of tumor necrosis factor-alpha (TNF α) release, inhibition of cell proliferation, induction of apoptosis and cell cycle arrest, as well as inhibition of lipoprotein oxidation, mediate the beneficial effects exerted by honey and its major components such as chrysin and other flavonoids [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some phenolics show antioxidant properties (16), due to chemical structures, that decrease the risk of oxidative diseases in humans (11). Honey contains phenolics collected by honeybees from plants along with nectar (17). Honey includes the phenolic acids and flavonoids such as protocatechuic acid, pcoumaric acid, and myricetin (18).…”
Section: Introductionmentioning
confidence: 99%
“…While hemoglobin levels it was found that the tested natural omani Honey, Natural Turkish Honey and Commercial Honey increased level up to 3 gm/dL. Honey administration trends to increase in Hb level may be due to honey as an anti-anemic and immunestimulant agent 20 .…”
Section: Physiological Effect Of Different Honey In Vivo On Micementioning
confidence: 90%